Prediction of Surface Roughness of Workpiece for Internal Gearing Power Honing Process and Variation Analysis - Ren Qiang; Xia Liang; Zhang Guozheng; Zhu Yonggang; Han Jiang (Jixie chuandong)
Honing has become an important method of gear finishing. It is of great significance to study the honing mechanism and accurately grasp the influence of honing speed and particle size on the roughness of the tooth surface in order to improve the surface quality of the machined gear. According to the characteristics of strong honing of inner gear honing gear， through the analysis of the relative motion of inner gear honing gear and workpiece， the linear velocity equation of each point on the surface of inner gear honing gear and machined workpiece is established. Based on the actual machining parameters， the classical grinding theory is applied to predict the roughness of honing workpiece， to explore the variation of roughness at different tooth heights on tooth surface， and to use three-dimensional morphology. The surface roughness of the gear of the internal meshing honing workpiece is measured， and the roughness prediction results and the measurement results are compared and analyzed. The results verify the law， which is of great significance to improve the honing quality.